An Analysis on Fixed Deposit Profit Rate and Interest Rate Between Islamic and Convensional Banks and the Effects to Bank's Performance - Mohd Saad, N. (Universiti Sains Islam Malaysia, 2024)
This study evaluates the Malaysian fixed deposit profit rate offered by Islamic banking with fixed interest rate offered by conventional bank for the period of 2002-2006. The performance of the banks was monitored to determine the effects of fixed deposit profit rate and fixed deposit interest rate to the bank's performance. To analyze the performance of banks, secondary data gathered from the analysis of bank's annual report and Thompson DataStream for the performance proxies such as net profit margin (NPM), return on equity (ROE) and return on invested capiyal (ROIC). The regression result found that tehre is a strong relationship between the bank's performances with their fixed deposits offered over the five years period. The results also indicates that the performance of conventional bank is out performs the Islamic bank. The study recommended that the bank could improve their profitability's performance with an improvement in fixed deposit rate offered to their customers in order to be competitive in the era of global world.